2018
DOI: 10.1016/j.eats.2018.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Multiligament Repair With Suture Augmentation in a Knee Dislocation With Medial-Sided Injury

Abstract: Knee dislocations often result in a severe multiligament injured knee (MLIK) with complex instability. Multiligament reconstruction can successfully restore knee stability and is commonly recommended, although surgical morbidity is induced by graft harvesting and tunnel drilling, and convergence of multiple tunnels can complicate the surgery. Therefore, as an alternative, primary repair of knee ligaments is currently reconsidered. The main advantages of primary repair consist of tissue preservation and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Multiple ligament knee injuries are rare; however, strong knee instability remains without proper treatment, and symptoms persist. Surgery is recommended for multiple ligament knee injuries as after conservative treatment, the rate of return to sports and work, the Lysholm score, the International Knee Documentation Committee (IKDC) score, and the Lachman test results are all inferior to those observed after surgical treatment [3]. However, there are no clearly established guidelines regarding surgical methods or the timing of surgery [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple ligament knee injuries are rare; however, strong knee instability remains without proper treatment, and symptoms persist. Surgery is recommended for multiple ligament knee injuries as after conservative treatment, the rate of return to sports and work, the Lysholm score, the International Knee Documentation Committee (IKDC) score, and the Lachman test results are all inferior to those observed after surgical treatment [3]. However, there are no clearly established guidelines regarding surgical methods or the timing of surgery [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although this type of injury is rare, accounting for less than 0.02% of orthopedic injuries [2], the instability of the knee results in persistent severe symptoms if appropriate treatment is not administered. Surgical treatment is recommended [3]; however, the specifications regarding the timing and surgical technique remain controversial. Few studies have reported on arthroscopic-combined single-stage repair [4].…”
Section: Introductionmentioning
confidence: 99%
“…The primary repair techniques for ACL and PCL tears will be discussed here, but have been previously described in more detail [18,32,33]. ACL and PCL repairs were all performed arthroscopically, using a Scorpion suture passer (Arthrex, Naples, FL).…”
Section: Primary Repair Techniquesmentioning
confidence: 99%
“…The primary repair techniques used for collateral ligaments are briefly described here as they have been previously described in more detail [18,36]. The medial and lateral extra-articular structures were treated first to enable fluid control during later knee arthroscopy.…”
Section: Primary Repair Techniquesmentioning
confidence: 99%
See 1 more Smart Citation